Electrochemical synthesis of AgNP and mechanical performance of AgNP-EG coatings on soft elastomer. (November 2020) - Mehdi, Murtuza; Akhtar, Maaz; Abro, Shahid; Qamar, Zahid; Nauman, Malik Muhammad; Aziz, Shahid; Khan, Zaib Ullah; Sufiyan, Muhammad; Waseem, Muhammad Bin; Azraf, Ali
Silver nanoparticles (AgNP) are being used extensively in medical and modern age stretchable and flexible electronics applications. In this article, we describe easy, cost-effective, and scalable synthesis of AgNP using electrolysis of pure silver metal in aqueous silver acetate solution. Size measurements and structural characterizations of the nanoparticles were performed using scanning electron microscopy coupled with image analysis and X-ray diffraction techniques, respectively. As-prepared nanoparticles were dispersed in pure ethylene glycol (EG) in a concentration of 50 wt%. The dispersion was coated on a soft, sticky, stretchable, and flexible elastomeric substrate polydimethylsiloxane (PDMS). Finally, the stretchability and flexibility tests on AgNP-EG/PDMS laminate were performed. The as-fabricated AgNP-EG/PDMS laminate is capable of stretching up to 18% without electrical failure. It was also found to remain electrically conductive when bent on curved surfaces. This behavior indicates that the AgNp-EG/PDMS laminate has good stretchability and flexibility and can be used as an electrically conductive platform for stretchable and flexible electronics.